Employers' expectations and observations on accounting interns' skills: a disparity analysis / Yunita Awang ... [et al.] - Awang, Yunita; Yusoff, Rohana; Abdul Aziz, Inayah; Yusoff, Yusliena (2012)
Internship provides a platform for the students to get real working exposure and for the employers to seek for the potential new employees. This study looked into the disparity between employers' expectation and observation on the skills of accounting interns in a public university. The study was conducted on 200 interns from Bachelor degree and Diploma level who have undergone internship in year 2008 and 2009, at various firms in several locations. For Bachelor of Accountancy interns, results from Wilcoxon Rank test indicate that there is evidence of disparity between expected and observed interpersonal skills and leadership skills. However for Diploma in Accounting Information System interns, evidences of disparity found to exist between expected and observed communication, intellectual, initiative taking, job attitude and leadership skills. Findings of this study will provide insight to the concerned public university and the universities at large, on the interns' capabilities from the employers' perspective.